Islamic social finance as catalyst to socio-economic sustainability: the role of fintech - Mohd Israil, Khaliq Ahmad; Yahaya, Muhamad Hasif (Routledge, Taylor & Francis Group, 2025)
This chapter is based upon the survey conducted during the course of doctorate degree, and the objective of the study is to analyse the contribution of the Islamic Social finance as a significant manifestation of the Islamic Financial system ensuring sustainable economic distribution of wealth by rich to the poor that is reflective of the Islamic economic system. This research is basically addressing Islamic social financing. Thus, this study has social implications to address the society’s poverty eradication scheme pertaining to the efficiency of zakat institutions in Malaysia for the speedier zakat payments to the recipients of zakat. However, other issues also arise particularly in using zakat funds by the zakat institutions. By right whatever expenditure the institutions incur from the zakat funds need to have the consent from the asnaf because of their religious and legal rights.